Machine Perfusion of Liver Grafts With Implantable Oxygen Biosensors: Proof of Concept Study in a Rodent Model. Issue 7 (July 2019) - Scheuermann, Uwe; Ibrahim, Mohamed M.; Yerxa, John; Parker, William; Hartwig, Matthew G.; Klitzman, Bruce; Barbas, Andrew S.
Abstract : Background: Normothermic machine perfusion (NMP) is emerging as a novel preservation strategy in liver transplantation, but the optimal methods for assessing liver grafts during this period have not been determined. The aim of this study was to investigate whether implantable oxygen biosensors can be used to monitor tissue oxygen tension in liver grafts undergoing NMP. Methods: Implantable phosphorescence-based oxygen sensors were tested in 3 different experimental groups: (1) in vivo during laparotomy, (2) during NMP of liver grafts with an acellular perfusate (NMP-acellular), and (3) during NMP with perfusate containing red blood cells (NMP-RBC). During in vivo experiments, intrahepatic oxygen tension was measured before and after occlusion of the portal vein (PV). In NMP experiments, intrahepatic oxygen tension was measured as a function of different PV pressure settings (3 vs 5 vs 8 mm Hg) and inflow oxygen concentration (95% O2 vs 6% O2 ). Results: In vivo, intrahepatic oxygen tension decreased significantly within 2 minutes of clamping the PV ( P < 0.05). In NMP experiments, intrahepatic oxygen tension correlated directly with PV pressure when high inflow oxygen concentration (95%) was used. Intrahepatic oxygen tension was significantly higher in the NMP-RBC group compared with the NMP-acellular group for all conditions tested ( P < 0.05). Conclusions: Implantable oxygen biosensors have potential utility as a tool for real-time monitoring of intrahepatic oxygen tension during NMP of liver grafts. Further investigation is required to determine how intrahepatic oxygen tension during NMP correlates with posttransplant graft function.